f(f(x)) = x

Algebra Level 3

Find the sum of all roots of the following equation.

( x 2 3 x + 3 ) 2 3 ( x 2 3 x + 3 ) = ( x 3 ) (x^2 -3x +3)^2 - 3(x^2 -3x +3) = (x-3)


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

The given equation simplifies to

( ( x 2 3 x + 3 ) 3 ) ( x 2 3 x + 3 ) = x 3 x ( x 3 ) ( x 2 3 x + 3 ) = x 3 ((x^{2} - 3x + 3) - 3)(x^{2} - 3x + 3) = x - 3 \Longrightarrow x(x - 3)(x^{2} - 3x + 3) = x - 3 \Longrightarrow

( x 3 ) ( x × ( x 2 3 x + 3 ) 1 ) = 0 ( x 3 ) ( x 3 3 x 2 + 3 x 1 ) = 0 ( x 3 ) ( x 1 ) 3 = 0 (x - 3)(x \times (x^{2} - 3x + 3) - 1) = 0 \Longrightarrow (x - 3)(x^{3} - 3x^{2} + 3x - 1) = 0 \Longrightarrow (x - 3)(x - 1)^{3} = 0 .

So x = 3 x = 3 is a single root and x = 1 x = 1 is a triple root, making the sum of all roots 3 + 1 + 1 + 1 = 6 3 + 1 + 1 + 1 = \boxed{6} .

There is no need to solve the equation to find the answer. The equation can be rewritten as x 4 6 x 3 + 12 x 2 10 x + 3 = 0 x^4-6x^3+12x^2-10x+3=0 ; the sum of its roots is equal to minus the coefficient of the second term.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...